2017
DOI: 10.1039/c7cp04493c
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry and dynamics of FHF anion in vacuum, in CD2Cl2 and in CCl4. Ab initio MD study of fluctuating solvent–solute hydrogen and halogen bonds

Abstract: FHF anion is a classic example of a central-symmetric strongly hydrogen bonded system that has been intensively investigated both experimentally and theoretically. In this paper we focus on solvent effects on symmetry, structure and dynamics of the anion. The FHF anion is studied in vacuum, dissolved in CHCl and dissolved in CCl by ab initio molecular dynamics simulations. We show that CHCl molecules form CHF hydrogen bonds with lone pairs of fluorine atoms, while CCl molecules form halogen bonds. These specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 81 publications
2
26
0
Order By: Relevance
“…20 Even the classic case of the bifluoride ion FHFcan be desymmetrized owing to fluctuations of the positions of solvent molecules. 21 Moreover, we concluded that there is no stabilization associated with symmetric, short, or low-barrier H-bonds.…”
Section: A•••h•••b Is Single-well or Double-well As Illustrated Inmentioning
confidence: 76%
“…20 Even the classic case of the bifluoride ion FHFcan be desymmetrized owing to fluctuations of the positions of solvent molecules. 21 Moreover, we concluded that there is no stabilization associated with symmetric, short, or low-barrier H-bonds.…”
Section: A•••h•••b Is Single-well or Double-well As Illustrated Inmentioning
confidence: 76%
“…In the gas phase, the stable linear structure of the (FHF) − anion is characterized by the F•••F distance of 2.304 Å with the H-atom located in its mid-point (infrared diode laser spectroscopy was applied for the analysis of this anion) [73]. However, other studies have shown that the environmental effects in solvent [74] or in crystals [75] may significantly influence this geometry. Particularly, in crystal structures, the D ∞h symmetry is often broken; for the sample of precise determined crystal structures, the range of F•••F distances from 2.194 Å to 2.382 Å is observed, the proton is often moved from the central position, and the system even loses linearity [75].…”
Section: Presents Histogram Of the O•••o Distances Of The O-h••mentioning
confidence: 99%
“…17b,18 Indeed, this interpretation was supported by computer simulations, 19 including the case of otherwise symmetric FHF -. 20 Further examples show that asymmetry is also seen in NHN and NHO H-bonds. 21 In summary, we and others have been unable to find evidence for symmetric Hbonds in solution (except at very low temperature, where the solvent becomes well ordered), 22 and with only one recent exception that demonstrates the subtlety of solvation.…”
Section: Introductionmentioning
confidence: 99%